The Policy of the Communist Party and Komsomol Concerning Informal Youth Associations In Ukraine (1986–1988) - Soroka, Svitlana (Pamięć i Sprawiedliwość, 2018)
The main objective of this paper is to analyze the Communist Party and Komsomol policy concerning informal youth associations in Soviet Ukraine. The author paid considerable attention to the factors that caused the emergence of informal associations’ phenomenon. It is shown that if up to the first half of the 1980s state structures preferred repressive methods of influence on informal youth associations, then from the mid-1980s onwards the policy of party-state leadership changed using the principle of cooperation according to a differentiated approach to associations. This led to a decrease in destructive activities of certain associations and overcoming tensions between the informal youth and public structures. However, in general, the authorities failed to establish constructive cooperation with informal youth associations. Informal organizations became politicized, opposition informal associations formed and consolidated in the second half of 1988. Their authority among the youth was growing amid the decay of official youth structures.